Elektroniczne doręczenia w postępowaniu administracyjnym - Czerwińska, Berenika (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Implementation of IT solutions in administrative proceedings serves to accelerate and facilitate citizens’ access to public services and ensures the most convenient citizen contact with the office thanks to the adaptation process of the institution to new technologies. The possibility of using an electronic method of service is an expression of adapting administration to the needs of modern society. The exercise of this institution is simple and gives the ability to settle the matter very quickly
Keywords: elektroniczne dostarczanie dokumentów; postępowanie administracyjne; prawo administracyjne